The Importance of the Neutrophil–Lymphocyte Ratio (NLR) and the Platelet–Lymphocyte Ratio (PLR) as Biomarkers for Differentiating Complicated and Uncomplicated Appendicitis - Michail Anastasakis; Ioannis Trevlias; Konstantinos Farmakis; Ioannis Valioulis (Diagnostics)
Background: This specific study evaluates the accuracy of two ratios, Neutrophil-to-Lymphocyte (N/L) and Platelet-to-Lymphocyte (P/L), as inflammatory markers on differentiating simple and complicated appendicitis preoperatively. Methods: The medical records of 341 children, up to 16 years old, with suspected acute appendicitis (AA) who underwent appendectomy, laparoscopic or open, between January 2020 and December 2022, in our department, were retrospectively reviewed. Routine blood exams and the demographic details were obtained. The area under the curve (AUC), sensitivity, and specificity of the above-mentioned markers regarding the differentiation of simple and complicated appendicitis, based on the statistical program SPSS, were calculated. Results: From the total of 341 patients, a percentage of 27.5% were related to perforated appendicitis, such as necrosis or the rupture of the appendiceal wall. A significant association was observed between perforated appendicitis and NLR values > 7.92, with concomitant sensitivity 62.5% and specificity 74.2%. Retrospectively, for PLR values > 180.57, the sensitivity was 61.1% and specificity 68.9%. For these models, the areas under the curve were 0.736 and 0.696. Conclusions: Our study revealed a significant association of N/L and P/L ratios with acute perforated appendicitis. Future studies should validate the use of these markers on this disease.